Influences of thermal annealing on P3HT/PCBM interfacial properties and charge dynamics in polymer solar cells. (5th November 2015) - Cheng, Cheng-En; Dinelli, Franco; Yu, Chen-Te; Shih, Hwa-Wei; Pei, Zingway; Chang, Chen-Shiung; Chien, Forest Shih-Sen
Abstract: The effects of thermal annealing on the interfacial properties of poly(3-hexylthiophene) (P3HT)/[6, 6]-phenyl C61 butyric acid methyl ester (PCBM) and on the charge dynamics in P3HT:PCBM polymer solar cells (PSCs) are investigated. This study determines that an effective phase separation of the P3HT and PCBM caused by thermal annealing achieves a larger interfacial area for efficient exciton dissociation and a well-defined pn junction with few defect levels at the P3HT/PCBM interface. Additionally, thermal annealing creates a compositional gradient across the P3HT:PCBM films, which enhances the charge transit ability significantly. These improved interfacial properties and efficiency in charge transit ability account for the better power conversion efficiency of P3HT:PCBM PSCs treated with thermal annealing.